2000
DOI: 10.1046/j.1365-2648.2000.t01-1-01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication and information needs of a random sample of community psychiatric nurses in the United Kingdom

Abstract: This paper reports on a cross-sectional survey investigating communication and information needs of community psychiatric nurses attached to community mental health teams in the United Kingdom. Community psychiatric nurses' access to and communication with other professionals was also assessed. In total, 200 teams were randomly sampled UK-wide, and postal questionnaires were sent to community psychiatric nurses attached to these teams; 110 questionnaires were completed and returned (55% response rate). Spearma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…The findings of Nochajski's (2001) study were consistent with other work; for example, Fakhoury and Wright (2000) explored the communication and information needs of a random sample of community psychiatric nurses (CPNs) in the UK using questionnaires distributed to 110 CPNs, with a response rate of 55%. The study was well designed and revealed concerns about the level of awareness of the CPNs about availability of services.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The findings of Nochajski's (2001) study were consistent with other work; for example, Fakhoury and Wright (2000) explored the communication and information needs of a random sample of community psychiatric nurses (CPNs) in the UK using questionnaires distributed to 110 CPNs, with a response rate of 55%. The study was well designed and revealed concerns about the level of awareness of the CPNs about availability of services.…”
Section: Resultssupporting
confidence: 79%
“…2004). However, some writers, such as Fakhoury and Wright (2000) and Nochajski (2001), have suggested primarily that good communication is needed to secure the success of teams. To explore this, Nochajski (2001) used a qualitative design with a convenience sample of 51 educators to gain insight into collaboration between professional groups who worked with students with disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation was the low numbers of returned questionnaires (only 31·6%) and low participation in the videotaped assessment, although the response rate for postal questionnaires in similar samples has been poor (for example, see Fakhoury & Wright 2000, Priebe et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…But skills required to work effectively as part of a team have seldom been addressed (Sainsbury Centre for Mental Health, 1997). As a result, the CPA was introduced with the expectation that collaborative teamwork existed when this was not necessarily the case (Simpson 1999, Fakhoury & Wright 2000, Miller & Freeman 2003). This has tended to exacerbate pre‐existing personality clashes and interprofessional tensions over status and changing roles (Mistral & Velleman 1997, Cott 1998, Norman & Peck 1999, Brown et al.…”
Section: Introductionmentioning
confidence: 99%